Ethics and ESG - Anona Armstrong (Australasian Accounting, Business and Finance Journal, 2020)
This paper provides theories, models and practices to assist in understanding ethical decision making in relation to environmental, social and governance issues. It begins by defining sustainability and how it is measured and reported. The most influential is the UN’s definition of sustainability and its measurement by compliance with its 17 Sustainability goals. In his recent report into the finance sector, the Royal Commissioner was scathing in his assessment of the lack of integrity, honesty and ethics and endorsed the importance of reporting non-financial indicators of performance. However, there are few explanations of the links in the literature between ethics and ESG and how ethical decisions could be managed. The purpose of this paper is to address this issue by exploring the questions: What are: ethics? Business ethics? The main ethical theories? What is the relationship between ESG and ethics? What is the difference between ethics and morals? How do we apply ethical reasoning to ESG?
Keywords: Sustainability; Ethics; Ethical reasoning